Phytochemical Analysis Of Babadotan Leaves Extract In Flour Beet Control - Solechatun, Solechatun; Widiyaningrum, Priyantini (Life Science, 2020)
Tribolium castaneum is one of the warehouse insects that attack post-harvest products. More flour beetles are found in processed post-harvest products such as wheat flour and rice flour. this is because wheat flour has a higher protein content. This study aims to determine the effect of Ageratum conyzoides leaf extract in controlling flour beetles. The design of this study is a complete one-way random design. This study uses 5 different concentrations. Namely 0%, 25%, 50%, 75% and 100%. Babadotan leaf extract was macerated using 96% ethanol. There are 10 flour beetles. To determine the effect of babadotan leaf extract, this observation was carried out using a Y-olfactometer. In addition to knowing what anti-insecta compounds contained in babadotan leaf extract, the extract was analyzed by phytochemical analysis by GC-MS method. The results of the analysis of the effects of babdotan leaf extract were analyzed by Anova one-way statistics and advanced LSD test. One-way Anova results showed a difference in the effect of the concentration of babadotan leaf extract. increasing the amount of concentration shows different effects of repellent. Based on the results of the study, the use of 100% babadotan leaf extract concentration gives a high repellent effect in controlling flour beetles. Kumbang tepung (Tribolium castaneum) adalah salah satu serangga gudang yang menyerang produk pasca panen. Kumbang tepung lebih banyak ditemukan pada produk pasca panen yang sudah diolah seperti tepung gandum dan tepung beras. hal ini dikarenakan tepung gandum memiliki kandungan protein yang lebih tinggi. penelitian ini bertujuan untuk mengetahui efek dari ekstrak daun babadotan dalam mengendalikan kumbang tepung. Rancangan penelitian ini adalah rancangan acak lengkap satu arah. Penelitian ini menggunakan 5 konsentrasi yang berbeda. Yaitu 0%;25%;50%;75% dan 100%. Esktrak daun babadotan di maserasi dengan menggunakan etanol 96%. Kumbang tepung yang digunakan sebanyak 10 ekor. Untuk mengetahui efek dari ekstrak daun babadotan maka pengamatan ini dilakukan dengan menggunakan olfaktometer bentuk Y. Selain itu untuk mengetahui senyawa anti insecta apa yang terkandung dalam ekstrak daun babadotan, maka ekstrak di analisis fitokimia dengan metode GC-MS. Hasil analisis efek ekstrak daun babdotan dianalisis statistika Anova satu arah dan uji lanjut BNT. Hasil Anova satu arah menunjukkan adanya perbedaan pengaruh konsentrasi ekstrak daun babadotan. pertambahan jumlah konsentrasi menunjukkan efek repelen yang berbeda-beda. Berdasarkan hasil penelitian, penggunaan konsentrasi ekstrak daun babadotan seesar 100% memberikan efek repelen tinggi dalam mengendalikan kumbang tepung